Amplify–Quantize–Forward Relay Channel With Quadrature Amplitude Modulation - Xianglan Jin (IEEE Access, 2022)
This paper considers an amplify–quantize–forward (AQF) relay channel with $M$ -ary quadrature amplitude modulation, where the relay implements a uniform quantization for the amplified received signal and forwards it to the destination. Two step-size determinant methods for the uniform quantization at the relay are proposed by deriving the power and the mean square error for the quantized signal. Given the step size, the maximum-likelihood detection is presented, and a linear combining detection called equivalent maximum ratio combining is proposed to reduce the detection complexity at the destination in the AQF relay channel. The simulation results confirm the superiority of the proposed quantization methods and detection algorithms.